Способ определения загрязненности снегового покрова радиоактивными компонентами - Язиков Е. Г. Егор Григорьевич; Таловская А. В. Анна Валерьевна; Судыко А. Ф. Александр Федорович; Филимоненко Е. А. Екатерина Анатольевна
опубл. 20.06.12